Pharmaceuticals in the environment pose the global threat – the state and the perspectives - Ćurčić, Marijana (Archives of Pharmacy, 2022)
The idea on global threat from pharmaceuticals present in the environment comes from the data on their annual commercial production, which amounts to more than 4000. Sum of commercially produced pharmaceuticals for humans or animals could be expressed in hundreds of tons. After application, pharmaceuticals can be metabolized, while parent compounds and their metabolites can be released into the environment and further metabolized through biotic and abiotic processes in water, soil, or even air. Therefore, from one active pharmaceutical substance, a set of active or inactive metabolites could be produced in the environment. The concentration of pharmaceuticals and their metabolites in the environment ranges between ng/L to µg/L. Active substances are made purposely to be physiologically active. A single pharmaceutical or its metabolites may not cause any adverse effect. However, total amount of these substances with common mechanism of action could become a point of public concern. Moreover, low biodegradability and persistency of pharmaceuticals make them chronically toxic to ecosystem, including humans. Therefore, removal of the active pharmaceuticals and their metabolites from the environment is one of the crucial points for the policy makers, researchers, and general population. Otherwise, exposure to the set of metabolites and parent substance can occur and lead to adverse effect in humans and environment as a results of exposure to antibiotics, cytostatic, hormones, antidepressants etc..